Construction of Water Table Contour Map and Geo Hydrological Studies on Krishnagiri Using GIS Techniques - Subramani, T; Mathialagan, S (International Journal of Engineering and Technology, 2018)
Geo-hydrology and groundwater exploration manner to pick out and to find the zone of recharge of groundwater in a precise river basin or a catchment .water level contour traces (or waft traces) are much like topographic strains on a map. They fully represent "elevations" in the subsurface. Water table contour lines can be used to inform which manner groundwater will glide in a given region. Plenty of wells are drilled and the hydraulic head is measured in each one. Water desk contours are drawn that be a part of areas of identical head .The ones water table contours lines are also called equipotential strains. Bear in mind: groundwater usually movements from a place of the higher hydraulic head to an area of decrease hydraulic head, and perpendicular to equipotential traces. In our challenge, we put into effect concept of water table contour map and geohydrological studies on Krishnagiri using GIS software program which plays the essential position in contemporary technology.Â Â